Pengaruh Perbandingan Modified Cassava Flour (Mocaf) dan Puree Nanas (Ananas Comocus) terhadap Karakteristik Sponge Cake - Valantino Soumokil, Rivaldo Socrates; Ari Yusasrini, Ni Luh; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
This study aims to determine the effect of the ratio of mocaf with pineapple puree on the chemical and sensory characteristics of sponge cake and to determine the proper ratio of mocaf with pineapple puree to produce steamed sponge cake with the best characteristics. The addition of pineapple to the process of making sponge cake from mocaf can be in the form of pineapple puree, because it will be easier to apply and the nutritional content of pineapple can be maintained. This experimental design used a completely randomized design with a comparison treatment between mocaf and pineapple puree, which consisted of 4 types of comparisons, the comparisons are 100%:0% (P0), 95%:5% (P1), 90%:10% (P2), and 85:15% (P3). This research was repeated four times, resulting in 16 trial experiments. The data obtained were then analyzed by means of variance, and if the treatment had a significant effect, it would be continued with Duncan's Multiple Range Test. The results of this study indicate that the comparison of mocaf with pineapple puree has a significant effect on moisture content, ash content, vitamin C content, crude fiber content, total carotenoids, antioxidant activity, expanding/raising power, aroma (hedonic test), color (hedonic test), taste (scoring and hedonic test), texture (score and hedonic test), and overall acceptance. The best content characteristics obtained in the comparison between mocaf with pineapple puree were 85%:15%, with characteristics of the moisture content of 29.80%, ash content of 0.35%, vitamin C content of 11.65 mg/g, crude fiber content of 7.5%, total carotenoids of 0.40 mg/g, antioxidant activity of 45.44%, and expanding/raising power of 62.16%. Sensory characteristics of the treatment with 15% pineapple puree sponge cake included preferred aroma, preferred color, slightly distinct pineapple taste, liked, soft texture, disliked, and overall acceptability.